Gambaran Karakteristik Klinis dan Faktor Paparan Debu pada Pasien Rhinitis Alergi Poli THT RS Royal Prima Medan Tahun 2025 - Siti Rahmah Panggabean; Cut Elvira Novita; Ferdinando Motuho Baeha (SENTRI: Jurnal Riset Ilmiah, 2025)
This study aimed to determine the relationship between dust exposure factors and clinical characteristics with the incidence of allergic rhinitis among patients at the ENT Clinic of Royal Prima Hospital Medan in 2025. This research employed a descriptive-analytic design with a cross-sectional approach. The study sample consisted of 50 patients selected using a purposive sampling technique. Data were collected through interviews using a structured questionnaire and clinical observation. Data analysis was conducted using univariate analysis to describe frequency distribution and bivariate analysis using the Chi-Square test to determine the relationship between variables. The results showed that the majority of respondents were within the productive age range (18–53 years) and were male (60%). The most common clinical symptoms were nasal obstruction (34%) and itching of the nose or eyes (42%), with most patients experiencing moderate severity levels (60%). Most respondents reported frequent dust exposure (60%) with a duration of six months or more (76%). The statistical analysis revealed a significant relationship between dust exposure and the incidence of allergic rhinitis (p = 0.007), as well as between clinical characteristics and disease severity (p = 0.000). In conclusion, dust exposure and patients’ clinical characteristics have a significant association with the occurrence of allergic rhinitis.